2008
DOI: 10.1007/s10714-008-0623-7
|View full text |Cite
|
Sign up to set email alerts
|

Falling into a Schwarzschild black hole

Abstract: Consider a radially freely falling observer who plunges into a Schwarzschild black hole. In contrast to a static observer, he will have a different view of the black hole and of the outer sky. Furthermore, the relationship between the proper time of the falling observer and the proper time of a distant static observer differs from the relationship between the proper times of two static observers or two freely falling observers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…In axially symmetric, rotating case, the vacuum spacetime is determined by the Kerr-de Sitter (KdS) geometry [34]. In the spacetimes with the repulsive cosmological term (and the related solutions of the f(R) gravity), motion of photons is treated in a series of papers [35][36][37][38][39][40][41][42][43][44][45], while motion of test particles was studied in [15,31,. Oscillatory motion of current carrying string loops in SdS and KdS spacetimes was treated in [69][70][71][72][73][74][75].…”
Section: Introductionmentioning
confidence: 99%
“…In axially symmetric, rotating case, the vacuum spacetime is determined by the Kerr-de Sitter (KdS) geometry [34]. In the spacetimes with the repulsive cosmological term (and the related solutions of the f(R) gravity), motion of photons is treated in a series of papers [35][36][37][38][39][40][41][42][43][44][45], while motion of test particles was studied in [15,31,. Oscillatory motion of current carrying string loops in SdS and KdS spacetimes was treated in [69][70][71][72][73][74][75].…”
Section: Introductionmentioning
confidence: 99%
“…Eqs. (25), (26) and Fig. 4 show that the real part of the quasinormal resonant frequency, Re(ω), is an (almost linearly) monotonically increasing function of the dimensionless mass parameter of the scalar field µ.…”
Section: The Quasinormal Resonances Of Massive Scalar Fields In Tmentioning
confidence: 89%
“…The cosmological consequences of the relict cosmological constant have been studied both for the cosmological models [4], and the Einstein-Straus vacuola models [5][6][7][8][9][10][11], or the more general McVittie model [12] of mass concentrations immersed in the expanding universe [13][14][15][16][17][18][19]. It has been shown that the repulsive cosmological constant can have an important role also in astrophysical processes (optical effects, accretion, jets) related to supermassive black holes in active galactic nuclei [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. The role of the relict cosmological constant in motion of interacting galaxies has been studied in [39,40], using an appropriately defined Pseudo-Newtonian potential [41].…”
Section: Introductionmentioning
confidence: 99%
“…This is likely to be true, however, we argue that understanding any exact solution of general relativity deserves to be studied and their unlikeliness should not preclude us from doing so. Moreover, visualizing space-time is one of the best tools to understand some of their properties [17][18][19], and the more complicated the metric is, the more useful will the visualization tools be. This paper is therefore aimed at filling this gap, as well as exploring the variety of phenomena that arise when one considers the full set of parameters of the metric as well as its maximal analytic extension.…”
Section: Introductionmentioning
confidence: 99%